Unstable Without a Source: The Non-Diagnostic Triad in Hypotensive Blunt Trauma Victims - Reily, Robert; Simpson, Tyler; Evans, Morgan; Smith, Alison; Duchesne, Juan (Journal of Endovascular Resuscitation and Trauma Management, 2019)
Background: Current algorithms for resuscitation of blunt trauma patients rely on chest x-ray (CXR), pelvic x-ray (PXR), and focused assessment with sonography for trauma (FAST), to quickly elicit a source of major bleeding in the trauma bay. The non-diagnostic triad (NDT), defined as negative initial CXR, PXR, and FAST, complicates the management of the hypotensive blunt trauma victim. Currently, there are no evidence-based recommendations for management of hemodynamically unstable patients with NDT. Methods: Hypotensive blunt abdominal trauma without a source was defined as a systolic blood pressure below 100 mmHg with NDT. Retrospective chart review was performed to characterize patient demographics, injuries, and outcomes. Subgroup analysis was performed to compare NDT patients with and without severe injury. Results: We reviewed 649 hypotensive blunt trauma victims. A total of 47 patients (33 males, 14 females) with a mean age of 40.0 years (standard error of the mean 2.5) had NDT upon initial assessment. Of the NDT group, 19/47 (40.4%) were found to have a major injury contributing to hypotension, while 28/47 (59.6%) were not diagnosed with a severe injury that could contribute to hypotension. Conclusions: Hypotensive blunt trauma patients with NDT are a unique and difficult population to diagnose and resuscitate. The majority of NDT patients lack significant injury. Among the severely injured NDT patients, acute blood loss was common and the potential utility for resuscitative endovascular balloon occlusion of the aorta in these patients warrants future study.